Simple method for computing scattered radiation in breast tomosynthesis. Issue 11 (9th September 2019) - Diaz, Oliver; Elangovan, Premkumar; Young, Kenneth C.; Wells, Kevin; Dance, David R.
Abstract : Purpose: Virtual clinical trials (VCT) are a powerful imaging tool that can be used to investigate digital breast tomosynthesis (DBT) technology. In this work, a fast and simple method is proposed to estimate the two‐dimensional distribution of scattered radiation which is needed when simulating DBT geometries in VCTs. Methods: Monte Carlo simulations are used to precalculate scatter‐to‐primary ratio (SPR) for a range of low‐resolution homogeneous phantoms. The resulting values can be used to estimate the two‐dimensional (2D) distribution of scattered radiation arising from inhomogeneous anthropomorphic phantoms used in VCTs. The method has been validated by comparing the values of the scatter thus obtained against the results of direct Monte Carlo simulation for three different types of inhomogeneous anthropomorphic phantoms. Results: Differences between the proposed scatter field estimation method and the ground truth data for the OPTIMAM phantom had an average modulus and standard deviation of over the projected breast area of 2.4 ± 0.9% (minimum −17.0%, maximum 27.7%). The corresponding values for the University of Pennsylvania and Duke University breast phantoms were 1.8 ± 0.1% (minimum −8.7%, maximum 8.0%) and 5.1 ± 0.1% (minimum −16.2%, maximum 7.4%), respectively. Conclusions: The proposed method, which has been validated using three of the most common breast models, is a useful tool for accurately estimating scattered radiation in VCT schemes used to study current designs of DBT system.